The Pro-neurogenic Effects of Cannabidiol and Its Potential Therapeutic Implications in Psychiatric Disorders - Luján, Miguel Á.; Valverde, Olga (Frontiers in Behavioral Neuroscience, 2020)
During the last decades, researchers have investigated the functional relevance of adult hippocampal neurogenesis in normal brain function as well as in the pathogenesis of diverse psychiatric conditions. Although the underlying mechanisms of newborn neuron differentiation and circuit integration have yet to be fully elucidated, considerable evidence suggests that the endocannabinoid system plays a pivotal role throughout the processes of adult neurogenesis. Thus, synthetic, and natural cannabinoid compounds targeting the endocannabinoid system have been utilized to modulate the proliferation and survival of neural progenitor cells and immature neurons. Cannabidiol, a constituent of the Cannabis Sativa plant, interacts with the endocannabinoid system by inhibiting fatty acid amide hydrolase activity (the rate limiting enzyme for anandamide hydrolysis), allosterically modulating CB1 and CB2 receptors, and activating components of the ‘extended endocannabinoid system’. Congruently, cannabidiol has shown prominent pro-neurogenic effects and, unlike Δ9-tetrahydrocannabinol, it has the advantage of being devoid of psychotomimetic effects. Here, we first review pre-clinical studies supporting the facilitating effects of cannabidiol on adult hippocampal neurogenesis and available data disclosing cannabinoid mechanisms by which cannabidiol can induce neural proliferation and differentiation. We then review the respective implications for its neuroprotective, anxiolytic, antidepressant, and anti-reward actions. In conclusion, accumulating evidence reveals that, in rodents, adult neurogenesis is key to understand the behavioral manifestation of symptomatology related to different mental disorders. Hence, understanding how cannabidiol promotes adult neurogenesis in rodents could shed light upon translational therapeutic strategies aimed to ameliorate psychiatric symptomatology dependent on hippocampal function in humans.